Experimental and Theoretical Investigations Regarding the Thione–Thiol Tautomerism in 4-Benzyl-5-(thiophene-2-yl)-2,4-dihydro-3H-1,2,4-triazole-3-thione - Sarac, K.; Orek, C.; Koparir, P. (Pleiades Publishing Ltd, 2021)
The title compound was synthesized by ring-closure reaction of thiophene-2-carbohydrazide with benzyl isothiocyanate and characterized using spectroscopic methods (NMR and FT-IR). Quantum chemical calculations at the B3LYP/6-311++G(d,p) level were carried out to examine its molecular and spectroscopic properties, thione–thiol tautomerism, and proton transfer reaction. The structural and spectroscopic results were well consistent with the experimental data. The solvent effect on the proton transfer reaction was examined using three solvents (acetone, ethanol, and dimethyl sulfoxide) through the polarizable continuum model (PCM) approximation (direct solvent effect) and solvent-assisted mechanism. A high energy barrier was determined for the interconversion of the thione and thiol forms in both gas and solution phases. Even though the presence of solvent molecules significantly reduced the barrier to proton transfer, it was insufficient for the reaction to occur. The corresponding thermodynamic parameters and the energy difference between the HOMO and LUMO of the thione and thiol tautomers were calculated.